2014
DOI: 10.1101/002816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread signals of convergent adaptation to high altitude in Asia and America

Abstract: Living at high altitude is one of the most difficult challenges that humans had to cope with during their evolution. Whereas several genomic studies have revealed some of the genetic bases of adaptations in Tibetan, Andean, and Ethiopian populations, relatively little evidence of convergent evolution to altitude in different continents has accumulated. This lack of evidence can be due to truly different evolutionary responses, but it can also be due to the low power of former studies that have mainly focused o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 84 publications
4
52
0
Order By: Relevance
“…This finding suggests an alternative strategy to supply the TCA cycle with succinate. Intriguingly, recent analysis of a large SNP dataset from low-and high-altitudeadapted populations in the Americas and Asia (31) aimed to identify pathways of convergent evolution, and highlighted fatty acid ω-oxidation as the most significant cluster of overlapping gene sets between high-altitude groups (32). ω-Oxidation is normally a minor pathway in vertebrates, becoming more important when β-oxidation is defective (33); through successive cycles, it oxidizes fatty acids to adipate and succinate in the endoplasmic reticulum, after which succinate enters the mitochondria with anaplerotic regulation of the TCA cycle (34).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests an alternative strategy to supply the TCA cycle with succinate. Intriguingly, recent analysis of a large SNP dataset from low-and high-altitudeadapted populations in the Americas and Asia (31) aimed to identify pathways of convergent evolution, and highlighted fatty acid ω-oxidation as the most significant cluster of overlapping gene sets between high-altitude groups (32). ω-Oxidation is normally a minor pathway in vertebrates, becoming more important when β-oxidation is defective (33); through successive cycles, it oxidizes fatty acids to adipate and succinate in the endoplasmic reticulum, after which succinate enters the mitochondria with anaplerotic regulation of the TCA cycle (34).…”
Section: Resultsmentioning
confidence: 99%
“…Two versions of BayeScan (16,35) were used to identify candidate targets for positive selection. Both versions assume an island model in which the subpopulations' allele frequencies are correlated through a common migrant gene pool from which they may differ in varying degrees.…”
Section: Methodsmentioning
confidence: 99%
“…Searching for selection footprints using a Bayesian approach taking into account population structure (Foll et al 2014) identified 156 outlier loci significantly associated with deltamethrin resistance. These outlier loci included 31 nonsynonymous variants and affected multiple supercontigs spread over all chromosomes.…”
Section: Polymorphisms Associated With Deltamethrin Resistancementioning
confidence: 99%
“…Searching for selection footprint using a hierarchical Bayesian approach BayeScan3 was used for identifying loci under natural selection through a hierarchical Bayesian model, taking into account population structure and usable on pools of individuals (Foll et al 2014). This approach estimates the probability that each locus is subject to selection by discriminating population-specific and locus-specific components of the fixation index using a logistic regression.…”
Section: Polymorphism Calling and Population Structurementioning
confidence: 99%